Assessment of Soil Quality Index for Tea Cultivated Soils in Ortaçay Micro Catchment in Black Sea Region - Orhan Dengiz; Ali İmamoğlu; Sekan İç; Fikret Saygın (Journal of Agricultural Sciences)
The objective of this research was to determine soil quality by taking into consideration the integrated Soil Quality Index (SQIw) model on tea plantations located in Ortaçay Micro Catchment of Rize. In the SQIw model, soil indicators were weighted by means of the Analytical Hierarchy Process (AHP). Various indicator units were normalized by a Standard Scoring Function. A total of 22 soil quality indicators were included in the SQIw model by grouping into 4 criteria which are; i-soil physical properties, ii- soil chemical properties, iii-macronutrient elements, iv- micronutrient elements. Twenty eight soil samples were collected from tea cultivated gardens including dominantly Leptosol and Alisol-Acrisol great soil groups based on FAO/WRB classification. The results indicated that 25% of the soil samples studied had weak quality level, whereas 75% were in moderate SQIw class in terms of tea requirements of the soil quality.